A catalogue of neighbor balanced designs in circular: Blocks of size 4 - Fariha Yasmin; Rashid Ahmed; Munir Akhtar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Neighbor balanced designs ensure that treatments comparisons will not be much affected by neighbor effects, therefore, these designs are more useful to remove the neighbor effects in experiments where the performance of a treatment is affected by the treatments applied to its adjacent plots. In this article, a catalogue of neighbor balanced designs is presented in circular blocks of size 4 for 4 < v <100.
Keywords: 330; Binary blocks; circular blocks; neighbor effects; neighbor designs